Fluid and electrolyte transport in rhesus monkeys challenged intracecally with Shigella flexneri 2a. - Kinsey, M D (1976)
Shigella flexneri 2a is an invasive enteric pathogen that may produce diarrhea when ingested by human beings and subhuman primates. We have previously shown that shigella diarrhea correlates with water and electrolyte transport abnormalities in the jejunum and colon. Dysentery alone is associated only with colonic transport abnormalities. To define the relationship between invasion and inflammation of the colon and the occurrence of jejunal transport abnormalities, we studied water and electrolyte transport, histology, and bacteriology in rhesus monkeys that were infected by introducing S. flexneri 2a directly into the cecum. In contrast to the pattern of disease seen after oral administration, cecal inoculation resulted in clinical disease in 64% of animals, of which 94% manifested dysentery alone, rarely preceded by mild diarrhea. Histologically, invasion and inflammation was limited to the colon. Secretion of water and sodium occurred in the colon of infected monkeys when compared with controls, whereas transport was normal in the jejunum and ileum. These data further demonstrate that severe dysentery can result from cecal injection of shigellae, but also suggest that the occurrence of watery diarrhea requires and may result from an undefined interaction between the jejunal mucosa and the organisms during transit through the small intestine.